Hubungan Antara Kompetensi Dan Penerapan Sistim Manajemen Mutu Dengan Kepuasan Kerja Karyawan - Supriyatno (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
This research was conducted to analyze the Competency and System Applied Quality Management ISO 9001: 2000 about Employee Satisfaction Work in Mercu Buana University at Jakarta. A survey method was used during this research in which questionnaires were distributed to the respondents. The hypothesis analysis used the technique of simple and multiple regression and was followed by the correlation. Using the Computer Program of SPSS (Statistical Product Service and Solution) with n = 103 (respondents) and t-table = 0.195, the result showed that there was less influence between Competency and System Applied Quality Management ISO 9001: 2000 to the Employee Satisfaction Work either Independent or concurrently. The Determinant Coefficients or Competency and System Applied Quality Management ISO 9001: 2000 about Employee Satisfaction Work were 0.250 and 0.348. This means the effects of Competency and System Applied Quality Management ISO 9001: 2000 about Employee Satisfaction Work were 25% and 34.8% and the largely influenced by the factors. The Determinant Coefficients of Competency and System Applied Quality Management ISO 9001: 2000 about Employee Satisfaction Work was 0.420. This means the effects of Competency and System Applied Quality Management ISO 9001: 2000 concurrently about Employee Satisfaction Work was 42% and the 58% Influenced Â by other factors.